Indigenizing International Law Education - Jonathan Liljeblad (Washington University Global Studies Law Review, 2025)
Law schools in countries as diverse as Australia, Canada, New Zealand, and the United States are engaging in movements to promote greater inclusion of Indigenous subject matter. In seeking to “indigenize” legal education, such efforts aim to integrate Indigenous voices and content into legal discourses. The inclusion of Indigenous subject matter, however, presents law schools with the challenge of identifying approaches appropriate for Indigenous concerns. Specifically, Indigenous rights movements call for strategies that push forward inter-cultural competency while seeking to move away from historical colonial legacies of scholarship that marginalized Indigenous peoples. To the extent that law schools maintain historical traditions of scholarship, they are at risk of perpetuating such colonial legacies. Complicating the positions of law schools are their connections to legal systems with colonial origins, which leave law schools in danger of reinforcing colonial orientations that can suppress Indigenous interests. The issues are exacerbated with the teaching of international law. Critics charge the prevailing international legal system with being a reflection of Western-based imperial expansion that sought the subjugation of Indigenous civilizations, making the teaching of international law a potential continuation of domination against Indigenous peoples. As a result, there is a need for guidance to help law schools with decision-making vis-a-vis the teaching of Indigenous subject matter, particularly for courses like international law. The present analysis responds to such a call, with the analysis formulating a framework to clarity strategies for the integration of Indigenous subject matter into the teaching of international law to appropriately address Indigenous concerns.
Keywords: law school; education; inclusion; indigenous; indigenous subjects; inter-cultural competency; colonial legacies; scholarship